2020
DOI: 10.1155/2020/2159363
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combinations of Ophthalmic Viscosurgical Devices and Suction Flow Rates on the Corneal Endothelial Cell Damage Incurred during Phacoemulsification

Abstract: We examined the effects of different ophthalmic viscosurgical devices (OVDs) and suction flow rates during phacoemulsification on the amount of ultrasound power used and damage to the corneal endothelium. In total, 48 eyes of 24 patients who underwent phacoemulsification and intraocular lens insertion with different OVD settings in the left and right eye between February and August 2018 were examined retrospectively from medical records. Each of the following types of OVDs was used in either the right or left … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Other factors can decisively contribute to decreasing postoperative endothelial cell loss, such as fluidics and instrument manipulation within the anterior chamber. 15,16 Also, other variables have been described to contribute to reducing the endothelial cell count postoperatively, including the anterior chamber depth, axial length, and intraocular lens design and location. In this regard, Khalid [17][18][19][20][21] measured the impact of such factors on endothelial injury after a phacoemulsification procedure and suggested that the phaco-chop technique is superior in energy efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors can decisively contribute to decreasing postoperative endothelial cell loss, such as fluidics and instrument manipulation within the anterior chamber. 15,16 Also, other variables have been described to contribute to reducing the endothelial cell count postoperatively, including the anterior chamber depth, axial length, and intraocular lens design and location. In this regard, Khalid [17][18][19][20][21] measured the impact of such factors on endothelial injury after a phacoemulsification procedure and suggested that the phaco-chop technique is superior in energy efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…We initially identified a total of 1,111 records through the systematic search, and after screening the study titles and abstracts, 12 potential articles (4,(9)(10)(11)(12)(13)(20)(21)(22)(23)(24)(25) were evaluated for final eligibility. Of these potential records, we excluded two studies which were not designed as randomized controlled trials (23,24), one study lacking comparisons between high-flow and low-flow phacoemulsification cataract surgery (25), and three studies without final reports (20)(21)(22). Ultimately, in this systematic review and meta-analysis, we only included six reports (4, 9-13), with a total of 477 participants from six RCTs.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…At present, it is generally accepted that the methods to reduce corneal endothelial damage caused by phacoemulsification include: (1) control of diabetes mellitus, 5 (2) the “soft shell” technique using low molecular weight viscoelastic devices, 6 and (3) reasonable setting of phaco-dynamic parameters. 7 , 8 However, the effects of the above measures are relatively limited, especially for those with pre-operatively existed endothelial diseases.…”
Section: Introductionmentioning
confidence: 99%